1978
DOI: 10.1364/ol.3.000218
|View full text |Cite
|
Sign up to set email alerts
|

Coherent trapping of atomic populations

Abstract: It is often desirable in laser spectroscopy and isotope separation to extract as much as possible of an atomic or molecular population that is distributed among a number of ground-state sublevels and low-lying metastable levels.We describe a form of coherent trapping that occurs when multiple resonant laser beams are used to couple the various ground states to a common upper level. This effect prevents the extraction of the entire population. We then study the effect with two dye lasers and an atomic beam and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
248
0
7

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 730 publications
(265 citation statements)
references
References 3 publications
4
248
0
7
Order By: Relevance
“…The phenomenon is also called "coherent population trapping" [15] or "dark resonance" and has been demonstrated in many systems [16] including single trapped ions [17]. It belongs to a large class of quantum interference effects in multilevel systems [18] and can be understood as a destructive interference of the two pathways to the excited level [19].…”
Section: Ground State Laser Cooling Using Electromagnetically Inducedmentioning
confidence: 99%
“…The phenomenon is also called "coherent population trapping" [15] or "dark resonance" and has been demonstrated in many systems [16] including single trapped ions [17]. It belongs to a large class of quantum interference effects in multilevel systems [18] and can be understood as a destructive interference of the two pathways to the excited level [19].…”
Section: Ground State Laser Cooling Using Electromagnetically Inducedmentioning
confidence: 99%
“…This previous research showed the potential for other interesting phenomena in multilevel systems, such as transfer to higher bound and continuum levels [12], and development of techniques for efficient transfer to unpopulated Rydberg states [19], which is essential for further advancement on spectroscopy, collision dynamics, quantum memories [21] and photon control in quantum information processing [23]. Kuklinski et al [19] showed an extension to the Heisenberg picture which presents a solution of the Liouville equations that allows the computation of the relaxation processes during the evolution of population transfer in multilevel systems.…”
Section: Introductionmentioning
confidence: 91%
“…Studies on coherent population trapping (CPT) and electromagnetically induced transparency (EIT) set the basis for many coherent control techniques based on combined detuned lasers and adiabatic transfer [10][11][12][13][14][15][16]. The * Electronic address: carles.serrat-jurado@upc.edu concept of CPT was employed to demonstrate pumping of atomic systems in a particular state, and has been theoretically analyzed by Arimondo and Orriols [11] and Gray et al [12] based on the solution of the Bloch-like equations of motion for a 3-level system with applications in Sodium atoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An optically thin ensemble of three-level atoms in the lambda configuration becomes perfectly transparent when driven by two independent laser fields in two-photon resonance [23][24][25][26]. This is of especial importance in spectroscopic applications since, under these conditions, spontaneous emission from the upper level is completely absent.…”
Section: Introductionmentioning
confidence: 99%